Integrable Systems Related to Deformed so(5) - Dobrogowska, A.; Odzijewicz, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We investigate a family of integrable Hamiltonian systems on Lie-Poisson spaces L+(5) dual to Lie algebras soλ,α(5) being two-parameter deformations of so(5). We integrate corresponding Hamiltonian equations on L+(5) and T∗R⁵ by quadratures as well as discuss their possible physical interpretation.